REMOTE SENSING ANALYSIS OF THE EFFECT OF CLIMATE CHANGE AND PRECIPITATION ON CHLOROPHYLL-A VARIABILITY IN THE ROKAN RIVER ESTUARY AREA - Mulyadi, Fadli
Climate phenomena such as the Indian Ocean Dipole (IOD) and dynamic changes in the rainy season have various impacts on aquatic ecosystems. One significant impact is the increased runoff from land to receiving water bodies and the sedimentation that potentially contains organic parameters and nutrients from the River Basin to the estuary downstream. This phenomenon occurs in the Rokan River Estuary, where sedimentation increases nutrient content and leads to excessive phytoplankton growth, altering the trophic status of the river estuary. To understand and monitor the water conditions, it is important to conduct water quality monitoring and improve the management of the receiving water bodies. One method used is monitoring the trophic status through the bioindicator chlorophyll-a found in phytoplankton. Remote sensing using MODIS (Moderate Resolution Imaging Spectroradiometer) satellite has been utilized to monitor the variability of chlorophyll-a and Sea Surface Temperature (SST) in the Rokan River Estuary. The analysis of satellite imagery data shows that the concentration of chlorophyll-a in the waters of the Rokan River Estuary ranges from 2.501 to 7.3905 mg/m3, indicating a mesotrophic status. The observed range of SST is 29.22 to 32.14°C. Eutrophic conditions are detected in several months, especially in December. These eutrophic conditions are caused by wash-off effects from rainfall during the SON period (September-October-November). Furthermore, there is a lag-time effect that contributes to the simultaneous increase in trophic status following the peak of the rainy season in the Rokan River Estuary. To address the potentially detrimental eutrophic conditions in the aquatic ecosystem of the Rokan River Estuary, water body control measures are necessary. These control measures aim to minimize the negative impacts of excessive phytoplankton growth and changes in trophic status in the estuary. Therefore, directed and sustainable management measures need to be implemented to maintain the balance of the aquatic ecosystem and protect the biodiversity in the Rokan River Estuary and its surrounding areas. Water body control efforts should involve various stakeholders, including environmental authorities, local governments, and the local community. Possible actions include land use management in the River Basin to reduce erosion and sedimentation, erosion control techniques such as soil erosion prevention through vegetation planting, and management of agricultural and domestic waste to reduce nutrient loads entering the river. Additionally, education and awareness among the community regarding the importance of maintaining the balance of the aquatic ecosystem should be enhanced. Through awareness programs and active participation of the community in environmental management, a collective consciousness can be fostered to protect and preserve the Rokan River Estuary. In the long run, mitigation efforts for climate change should also be a primary concern. Reducing greenhouse gas emissions and implementing sustainable climate adaptation policies can help reduce the impacts of extreme climate phenomena and maintain the stability of the aquatic ecosystem. With these measures, it is hoped that the Rokan River Estuary can be restored from eutrophic conditions and maintain the sustainability of its aquatic ecosystem. Continuous monitoring, research, and cross-sector cooperation will be crucial in addressing the complex environmental challenges. Therefore, it is expected that the Rokan River Estuary will remain a healthy, sustainable aquatic ecosystem that benefits human life and biodiversity in its surroundings. Overall, climate phenomena such as the IOD and dynamic changes in the rainy season have significant impacts on aquatic ecosystems, particularly in the Rokan River Estuary. Water quality monitoring, water body control, and a better understanding of the interaction between climate and aquatic ecosystems are key to maintaining the sustainability and preservation of these aquatic ecosystems.